A tribute to Dean Francisco Benitez - Reyes, Pablo P. (Education Quarterly, 1953)
Delivered at the memorial celebration of the second anniversary of the death of Dean Francisco Benitez, June 30, 1953. Although Dean Francisco Benitez already passed away, he left a legacy, not just to teachers, but to all those he was able to reach through his works and words. An educator, who died in service, remains alive in the heart and memory of the people, especially by the Alumni of the UP College of Education.